The impact of the 2013 constitution on judicial independence: the case of Zimbabwe (2008-2014) - Makono, Delight (Midlands State University, 2017)
This research analyzed the impact of the 2013 constitution on judicial independence in Zimbabwe from 2008 to 2014. This study was taken against the contention that the 2013 people driven constitution is just a replica of the Lancaster House constitution which gave the executive branch to override the activities of the judiciary arm to the extent that the judiciary ends up operating as an the extension of the executive. The major cause for failure of the Lancaster House Constitution was the fact that it was riddled with the provisions which allowed the president to meddle in the activities of the judiciary. The researcher utilized the notion of separation of powers and the realism theory, this was employed in a bid to have a better understanding of the concept of judicial independence as well as some challenges which hinders its full realization in Zimbabwe. The research is highly qualitative and in sampling the respondents, the study utilized purposive sampling technique. The study concludes that, even though the 2013 constitution brought with it some positive changes, it is still detrimental to judicial independence because it still permits the executive particularly the president to meddle in the activities of the judiciary. The researcher calls for the need to further improve the freedom of the judiciary in the constitution through including provisions that distances the executive from the activities of the judiciary. The study recommends that there is need to raise awareness to the public on issues pertaining the constitution itself and the legal framework surrounding the judicial system. The research also suggests that there should be a provision in the constitution that guarantees the budget of the judiciary as a percentage of the national budget.